Perbandingan Kualitas Organoleptik Susu Kedelai Yang Menggunakan Metode Pengolahan Illinois dan Metode Pengolahan Pusbangtepa-IPB - Shania Florencia (JURNAL GASTRONOMI INDONESIA, 2020)
Soybean is a food that has a high source of vegetable protein. The development of food technology causes soybeans to be processed into a food source of choice for the community such as soy milk. Soy milk which is rich in nutrients is less attractive to the public due to its unpleasant taste and smell. This unpleasant taste and smell is caused by off-flavour compounds contained in soybeans. The illinois method and the pusbangtepa-IPB method are methods that can eliminate the unpleasant taste and odor of soy milk. Soy milk that has been processed by these two methods is a source of data for comparison. Organoleptic and sensory panel tests were used to test the aroma, taste, and color of soy milk. The results of processing soy milk with both methods produce soy milk without bad taste and odor, but the Illinois method is a more effective method. This method produces soy milk that does not have a bitter taste and a yellowish color (normal).